Application of numerical simulation studies to determine dynamic loads acting on the human masticatory system during unilateral chewing of selected foods - Stróżyk, Przemysław; Bałchanowski, Jacek (Frontiers in Bioengineering and Biotechnology, 2023)
This paper presents its kinematic-dynamic computational model (3D) used for numerical simulations of the unilateral chewing of selected foods. The model consists of two temporomandibular joints, a mandible, and mandibular elevator muscles (the masseter, medial pterygoid, and temporalis muscles). The model load is the food characteristic (i), in the form of the function Fi=f(hi) - force (Fi) vs change in specimen height (hi). Functions were developed based on experimental tests in which five food products were tested (60 specimens per product). The numerical calculations aimed to determine: dynamic muscle patterns, maximum muscle force, total muscle contraction, muscle contraction corresponding to maximum force, muscle stiffness and intrinsic strength. The values of the parameters above were determined according to the mechanical properties of the food and according to the working and non-working sides. Based on the numerical simulations carried out, it can be concluded that: (1) muscle force patterns and maximum muscle forces depend on the food and, in addition, the values of maximum muscle forces on the non-working side are 14% lower than on the working side, irrespective of the muscle and the food; (2) the value of total muscle contraction on the working side is 17% lower than on the non-working side; (3) total muscle contraction depends on the initial height of the food; (4) muscle stiffness and intrinsic strength depend on the texture of the food, the muscle and the side analysed, i.e. the working and non-working sides.